Exploring Smart Decision-Making through Games for Elementary School Students - IGA. Lokita Purnamika Utami; Wayan Ardana; Alexander Hamonangan (Jurnal Ilmiah Sekolah Dasar, 2025)
This study aims to measure the validity of the Smart Decision Game media as a learning tool for decision-making within the context of swimming sports training. The method used is Research and Development (R&D) employing the ADDIE model, which consists of the stages of analysis, design, development, limited implementation, and evaluation. Validation was conducted through structured interviews with swimming coaches and athletes to qualitatively assess the content feasibility, visual appearance, and functionality of the media. The results indicate that the Smart Decision Game media received very feasible ratings in terms of content, visualization, and relevance to the learning context. The content experts (swimming coaches) rated the validity with an average score of 3.87, while the media validity obtained an average score of 3.90, both falling into the very valid category. These findings suggest that the media has strong potential to be used as a decision-making learning aid aligned with the needs of the sports world, particularly in shaping strategic and responsive thinking patterns in athletes. This study provides an initial contribution to the development of contextual game-based educational media and encourages further research to test its practicality and effectiveness on a larger scale.